2018
DOI: 10.5121/ijaia.2018.9103
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Artificial Neural Networks and Fuzzy Logic Approaches for Crack Detection in a Beam Like Structure

Abstract: This paper proposes two algorithms of crack detection one using fuzzy logic (FL) and the other artificial neural networks (ANN

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…This study further adopted trainlm (lavernberg-Marquardt) in training the NN, although trainlm is the time taken, nevertheless, the algorithm is capable of attaining good generalisation. On the other hand, this study adopts learngm as the learning function for the NN, while the performance function adopted is the Mean Squared Error (MSE), which is in line with Hegde (2018).…”
Section: Training Of the Networkmentioning
confidence: 99%
“…This study further adopted trainlm (lavernberg-Marquardt) in training the NN, although trainlm is the time taken, nevertheless, the algorithm is capable of attaining good generalisation. On the other hand, this study adopts learngm as the learning function for the NN, while the performance function adopted is the Mean Squared Error (MSE), which is in line with Hegde (2018).…”
Section: Training Of the Networkmentioning
confidence: 99%
“…Kết quả so sánh giữa các giá trị dự kiến và 30 dữ liệu thử nghiệm cho thấy, với độ chính xác tốt hơn các công thức hiện có khác, mô hình ANN được phát triển dẫn đến các tham số thống kê được cải thiện. Ngoài ra, phương pháp này cũng được sử dụng trong nhiều nghiên cứu khác, ví dụ, trong [19], [20], hoặc Abambres và cộng sự [8], tác giả cũng đã sử dụng phương pháp ANN để nghiên cứu khả năng chịu tải của các dầm khoét lỗ chịu tác dụng của tải trọng phân bố đều với tám tham số đầu vào. Bên cạnh đó, hệ thống thần kinh mờ là ANFIS cũng là một thuật toán hiệu quả để dự đoán cường độ cắt của dầm [21].…”
Section: đặT Vấn đềunclassified
“…They presented the influence of the crack depth and location on natural frequencies. Gowd et al [7] found first three relative natural frequencies for an un-cracked and single cracked beam with using finite element method and used two algorithms using fuzzy logic and artificial neural networks for crack detection. They used the first three relative natural frequencies as three inputs and the corresponding relative crack depth and location as the two outputs in the algorithms.…”
Section: Introductionmentioning
confidence: 99%